Ocular Symptomatology On Continued Usage Of Electronic Gadgets In It Professionals - Subiksha, E. Johannah; Poornima, R. (Journal of Neonatal Surgery, 2025)
Aim: To prepare the profile of prevalence of ocular symptoms and their impact of the ergonomic structure of Electronic Visual Display Unit in work productivity among IT professionals in Tamil Nadu. Materials and Methods: An Online survey was conducted among IT professionals in Tamil Nadu. A total number of 150 people having a minimum exposure to computer of at least for 3 hours a day for more than 3 years was recruited in the study. Design – Cross sectional study. A convenient sampling was done to select subjects for the study. Participants were requested to fill the Questionnaire according to their ocular symptoms and ergonomic structure of their company. Data were collected by the questionnaire through email among computer users in Tamil Nadu. Results: A total of 150 subjects participated in the study. 71 (47.3%) were females and 79 (52.7%) were males. The mean age of study participants is 28.1. The symptoms most experienced by the study participants are Headache (38.7%), Eyestrain (37.3%) and Blurred vision (34%). Factors like Seating position, viewing distance, level of top of the screen, spectacle usage, habit of voluntary blinking were independently associated with computer vision syndrome. Conclusion: Working on Electronic Gadgets has brought about numerous lifestyle changes. There have been both positive and negative impacts as a consequence. The increase use of Gadgets has resulted in adverse health effects for individuals. Therefore, eliminating use of gadgets in impossible, whereas controlling it to appropriate levels will be useful.